EGGS AND EARLY LARVAE OF THE GREY MULLET VALAMUGIL SEHELI (FORSSKAL) - Bensam, P (Indian Journal of Fisheries, 2011)
Planktonic eggs coUoplcd from P^k.Bsy ,ancl Gulf of Mannar and identified circiunstantially as of Valamugil seheli (Forsskal) were reared in the laboratory up to the 72-h postlarvae. The eggs ranged in diameter from 0.621 mm to 1.09 mm and were with single, pigmented oilglobules ranging in diameter from 0.212 mm to 0.273 mm. The periviteUine space was narrow. The yolk, being neither sagmented nor vacuolated, was clear. Newly hatched larvae measured 2.179mm. They had black pigment spots on the dorsal side of the body, with a few localised, yellowish networks of xanthophores. In the 24-h larva, most of the black pigment spots had migrated to the ventral side of the body. The 48-h-old larva had its mouth formed, eyes pigmented, yolk utilized and pectoral fins developed, and so was in the early postlarval stage. In the 72-h larva there was iiicrease in pigmentation along both dorsal and ventral aspects of body. In this postlarval phase the number of myomeres had stabilized at 25, corresponding to the adult-vertebral number.